Landscape architecture design studio-based using process-evaluation model in open distance learning / Masbiha Mat Isa ... [et al.] - Mat Isa, Masbiha; Misni, Alamah; Ab Latif, Faridatul Akma (2021)
This study addresses landscape architecture design studio-based challenges during open distance learning (ODL) amid the COVID-19 pandemic. The research is being conducted at Universiti Teknologi MARA (UiTM), Selangor, Malaysia. Landscape Architecture Studio-based Process Evaluation Model (LASP) is generated primarily for online learning while sustaining the traditional/conventional methods and implementing it using available data-networking systems. This study shows the importance of the model for decision-making to support studios of landscape architecture design courses. This process-evaluation model was developed to help landscape architecture studio-based design and planning processes, especially in the macro-scale study of landscape planning. Moreover, it is designed to facilitate lecturers worldwide to structure their teaching in studio-based learning, simplify the work process, and maximize collaborations among students in the online design learning process. Students from a landscape planning studio used the model to track their workflows. According to students' self-evaluation and reflection, this LASP model significantly impacted their approaches to the design process and increased their awareness of individual progress while collaborating in micro-scale projects. This study also suggests that the right choice of available online mediums and platforms of big data contributes to improving students' desire, ability to work independently and with group members in the current pandemic COVID-19 education situation worldwide. However, while some might view existing online platforms as stagnant, the long-standing culture of creativity and innovative design in Landscape architecture design studios and professional online offices is almost certainly going to involve emerging new technologies. Furthermore, their possible future necessity will creatively use various technologically advanced design tools and data to impact the studio-based design, teaching and learning, and practices.